Double Allegiance: Digital Natives as Filmmakers - Jo Sondre Moseng; Håvard Andreas Vibeto (Universitetsforlaget, 2012)
This article is based on close examination of more than 300 films screened at the Amandus film festival for young filmmakers, in the 25 year period between 1987 and 2012. The aim of the article is to highlight some of the most striking developments in this data material - aesthetically as well as thematically. The overall argument is that the Amandus films display a double allegiance to commercial movies, both in terms of their semi-professional cinematic form and in terms of the themes and moral attitudes expressed.